Penyisihan BOD Dan TSS Pada Limbah Cair Kafetaria Menggunakan Emergent Macrophyte Wetlands dengan Tanaman Melati Air - Apria, Wahyu Salsa Fajar; Rosariawari , Firra; Sitogasa, Praditya Sigit Ardisty (Jurnal Serambi Engineering, 2025)
The rising trend of working from anywhere has increased activity in cafeterias, which produce wastewater with high levels of organic matter and suspended solids. If discharged without treatment, this wastewater can pollute the environment and disrupt ecosystem balance. This study aims to evaluate the effectiveness of plant quantity and retention time in a constructed wetland system of the sub-surface flow type, using the emergent macrophyte wetland method with amazon sword plant (Echinodorus palaefolius) plants to reduce Biochemical Oxygen Demand (BOD) and Total Suspended Solids (TSS) in cafeteria wastewater. Variations in plant quantity (12, 14, and 16 stems) were tested over a 16-day retention period. The results showed BOD removal efficiency ranging from 94.62% to 97.85%, while TSS reduction ranged from 73.3% to 97.8%, depending on the sampling time. In the best-case scenario (on day 4), the system reduced BOD from 185.9 mg/L to 6 mg/L and TSS from 150 mg/L to 3 mg/L, meeting the effluent quality standards for restaurant wastewater. This high efficiency is attributed to physical filtration through roots and substrate, as well as rhizospheric microbial activity supported by the roots of the Amazon sword plant (Echinodorus palaefolius).